Food Culture Studies in India
XXIV, 163 p. 1 illus.
Keywords: This book discusses food in the context of the cultural matrix of India. Addressing topical issues in food and food culture, it explores questions concerning the consumption, representation and mediation of food. The book is divided into four sections, focusing on food fads; food representation; the symbolic valence of food; modes and manners of resistance articulated through food. Investigating consumption practices in both public and ethnic culture, each chapter introduces a fresh approach to food across diverse literary and cultural genres. The book offers a highly readable guide for researchers and practitioners in the field of literary and cultural studies, as well as the sociological fields of food studies, body studies and fat studies.